Thickness Effect on the Optical Constants of Poly Methyl Methacrylate (PMMA) Doped by Potassium Iodide - Musa, Wasan A; Hamad, Tagreed K; Abdul Nabi, Mohammed T (Al-Nahrain Journal of Science, 2018)
Films of Poly Methyl Methacrylate (PMMA) doped by (1%) Potassium Iodide (KI) have been prepared using casting method at room temperature. Optical properties were investigated for different thicknesses by using spectrophotometeric measurement of absorption reflection transmission in the wave length range (200-800) nm. Both the refractive index (n) and absorption coefficient () were determined for the films. The optical dispersion parameters have been analyzed by single oscillator model. The value of Eo and Ed were found and the other parameters have been determined by Wemple-DiDomenico method